Xanthones from Calophyllum inophyllum - Ee, Gwendoline Cheng Lian; Jong, Vivien Yi Mian; Md. Sukari, Mohd Aspollah; Rahmani, Mawardi; Kua, Audrey Siew May (Universiti Putra Malaysia Press, 2009)
The roots of Calophyllum inophyllum (Guttiferae), furnished six xanthones which are rasilixanthone (1), 1,3,5-trihydroxy-2- methoxy xanthone (2), caloxanthone A (3), pyranojacareubin (4), caloxanthone B (5) and tovopyrifolin (6), Structural elucidations of these compounds, were achieved through 1D and 2D NMR and MS techniques. In this paper, the isolation and structural elucidation data for these xanthones are reported.